P J Hoedemaker: "Wat ék bedoel, is die behoud van die kerk" - Wyk, D. J. C. van (Hervormde teologiese studies, 1990)
P J Hoedemaker. ‘What I aim at, is the conservation of the church’ The birthday of the wellknown Dutch Reformed theologian P J Hoedemaker 150 years ago, was celebrated in the Netherlands during 1989. In his struggle against the formidable dr Abraham Kuyper, it became more and more evident that Hoedemaker was himself a very perspicacious, independent theologian. His dramatic struggle for the unity and the wholeness of the church against every schismatic action is really unique in the history of the church. The theological concepts of Hoedemaker strongly influenced the thoughts of Dutch theologians like Th L Haitjema and A A van Ruler, and consequently also a large number of South African theologians in the Dutch Reformed Churches.